The effects of chronic low dose exposure of chlorpyrifos on the rat kidney - Aung, Sanda; A.Talib, Norlelawati; Abdullah, Nor Zamzila; Mat Zainone, Zamzuria; Harun, Norra; Mohd Noor, Noriah; Abdul Razak, Tariq (International Islamic University Malaysia, 2020)
Introduction: An increased incidence of chronic kidney disease (CKD) was reported among agricultural workers who were exposed to organophosphates (OP). There is little information on the effects of chronic low OP exposure on kidney in experimental animals. Chlorpyrifos (CPF) is a common type of OP used in agriculture. Thus, the aim of this study was to assess the effects of chronic low subcutaneous exposure of CPF on the kidney. Methods. Eighteen male Sprague Dawley rats were divided into three groups, with six rats in each group. Group 1 served as a control group, and groups 2 and 3 received a subcutaneous vehicle (3% dimethyl sulfoxide + 97% v/v soy oil) or CPF (18.0 mg/kg) respectively, every other day for 180 days. Serum urea, creatinine, uric acid, cystatin C, electrolyte levels, acetylcholinesterase (AChE), and arylesterase (ArE) activities were measured. Histopathological changes in the kidney tissues were examined. Results. Urea, creatinine, uric acid, and cystatin C levels were significantly increased (p < 0.05), while electrolytes were reduced (p < 0.05) in the CPF - treated rats. Both AChE and ArE activities were depressed in the CPF group (p < 0.01 and p < 0.001, respectively). Diffuse necrosis of proximal tubules and glomerular hypercellularity were observed in the kidney in the CPF group. Conclusion. A chronic low dose of CPF via subcutaneous exposure caused considerable renal tubular necrosis and erangement of glomerular function. These findings suggest that chronic occupational OPs exposure can cause kidney damage.